2015
DOI: 10.1111/jan.12615
|View full text |Cite
|
Sign up to set email alerts
|

Nursing handovers as resilient points of care: linking handover strategies to treatment errors in the patient care in the following shift

Abstract: Nursing handover is an opportunity for nurses to prevent errors and unsafe practice by implementing more risk-aware handover strategies. Implications for facilitating the use of such strategies are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
70
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(75 citation statements)
references
References 71 publications
3
70
0
2
Order By: Relevance
“…Using a familiar oral handover structure gave the oncoming team a better grasp of the situation and made it easier to ask questions. In the literature, different handover models have been proposed to promote patient safety, reduce errors of omission and enhance the reliability of information transfer (Anderson et al., ; Drach‐Zahavy & Hadid, ; Johnson et al., ). Instead of looking for one model that can fit all handover situations, it is now argued that the structure of a handover should be tailored to the context of the clinical area and the needs of the staff members and that each unit should agree on which structure works best for the team (Staggers & Blaz, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a familiar oral handover structure gave the oncoming team a better grasp of the situation and made it easier to ask questions. In the literature, different handover models have been proposed to promote patient safety, reduce errors of omission and enhance the reliability of information transfer (Anderson et al., ; Drach‐Zahavy & Hadid, ; Johnson et al., ). Instead of looking for one model that can fit all handover situations, it is now argued that the structure of a handover should be tailored to the context of the clinical area and the needs of the staff members and that each unit should agree on which structure works best for the team (Staggers & Blaz, ).…”
Section: Discussionmentioning
confidence: 99%
“…An incomplete and poor handover can be dangerous for the patients’ safety (Mayor et al., ; Street et al., ). Thus, an oral handover is risky in the care process because information can be inaccurate, lost, distorted or misinterpreted (Drach‐Zahavy & Hadid, ; Holly & Poletick, ).…”
Section: Introductionmentioning
confidence: 99%
“…Nurse managers and leaders should promote positive relationships among staff. This can be achieved through the implementation of team‐building interventions such as TeamSTEPPS (Drach‐Zahavy & Hadid, ; Feraco et al., ), and through the promotion of a collegial work environment. Avoiding the use of agency or temporary staff may also improve continuity and opportunities for staff to build relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Internationally, handover communication is an important aspect of providing safe patient care, yet researchers have suggested that handover communication is often incomplete and/or inaccurate (Kerr, Lu, McKinlay, & Fuller, ; McCloughen, O'Brien, Gillies, & McSherry, ; Meissner et al., ; Ong, Biomede, & Coiera, ). It has been documented that poor quality or ineffective shift handover can result in negative consequences for patients, staff and healthcare organizations (Australian Council for Safety and Quality in Health Care, , Drach‐Zahavy & Hadid, ; Kitch et al., ; Meissner et al., ; Moon, Gonzales, Woods, & Fox, ). Although there is considerable literature addressing factors that influence handover quality or effectiveness, few studies have empirically tested those factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation